Answer:
you have to subtract those two numbers
Answer: uh.. 3?
Step-by-step explanation:
lol
Summation of 3n + 2 from n = 1 to n = 14 = (3(1) + 2) + (3(2) + 2) + (3(3) + 2) + . . . + (3(14) + 2) = 5 + 8 + 11 + ... + 44 ia an arithmetic progression with first term (a) = 5, common difference (d) = 3 and last term (l) = 44 and n = 14
Sn = n/2(a + l) = 14/2(5 + 44) = 7(49) = 343
Therefore, the required summation is 343.
Answer:
Exponential Decay
Step-by-step explanation:
It's exponential growth when your base value is > 1. Example:
1.3ˣ, 2ˣ, 7ˣ, 999ˣ
It's exponential decay when the base value is < 1. Example:
0.9ˣ, 0.45ˣ, (1/2)ˣ, 0.79ˣ, .999ˣ
It's neither when the base value = 1. Example:
1ˣ
Answer:
270
Step-by-step explanation:
becasue 100 percent of 90 would be 90
![100*3=300](https://tex.z-dn.net/?f=100%2A3%3D300)
so multiply
![90*3=270](https://tex.z-dn.net/?f=90%2A3%3D270)